Exploring the driving mechanisms behind the formation of agricultural science and technology innovation clusters: a case study of Lanling County, China - Xie, Ailiang; Yang, Youbao; Che Leh, Fauziah; Rambeli, Norimah; Miao, Yingfan (Frontiers in Sustainable Food Systems, 2025)
This study examines the mechanisms underlying the formation and development of agricultural science and technology innovation clusters, using Lanling County in China as a representative case. It addresses how localized innovation strategies contribute to rural industrial transformation within the broader context of national agricultural modernization. Employing a qualitative case study approach, the research integrates field observations, semi-structured interviews, and document analysis. The analytical framework is informed by industrial cluster theory and the regional innovation systems perspective. The study identifies and examines the interactive dynamics among four major drivers: natural and socioeconomic resource endowments, market demand, policy support, and technological innovation. The findings reveal that the emergence and consolidation of the Lanling vegetable innovation cluster is the outcome of synergetic interactions between endogenous innovation capabilities and exogenous enabling conditions. Strategic interventions—such as the construction of intelligent greenhouses, the expansion of specialized production bases, cooperative organization development, and the implementation of quality control systems—have collectively advanced the region's agricultural upgrading. The study contributes to theoretical discourse by extending cluster theory to the agricultural sector and illustrating the applicability of regional innovation systems in rural contexts. Practically, it offers policy-relevant pathways including the enhancement of technological service networks, market responsiveness, environmental governance, and enterprise collaboration. The research provides replicable insights for other regions seeking to promote sustainable agricultural transformation through innovation-driven development.